An Analysis of Convolutional Neural Networks for Sentence Classification - Vieira, João Paulo A. (2017)
Over the past few years, neural networks have reemerged as powerful machine-learning models, yielding state-ofthe- art results in fields such as image recognition and speech processing. More recently, neural network models started to be applied also to textual natural language signals, again with very promising results. This paper show a series of experiments with Convolutional Neural Networks for sentence-level classification tasks with different hyperparameter settings and how sensitive model performance is to changes in these configurations.